2011
DOI: 10.1186/1471-230x-11-87
|View full text |Cite
|
Sign up to set email alerts
|

An australian audit of vaccination status in children and adolescents with inflammatory bowel disease

Abstract: BackgroundChildren and adolescents with inflammatory bowel disease (IBD) are at increased risk of vaccine preventable diseases (VPD). This includes invasive pneumococcal disease and influenza. The primary aim of this study was to describe compliance with current Australian guidelines for vaccination of children and adolescents diagnosed with IBD. A secondary aim was to review the serological screening for VPD.MethodsA random sample of patients (0-18 years at diagnosis), were selected from the Victoria Australi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 38 publications
0
22
3
Order By: Relevance
“…All previously published studies assessing the seasonal influenza vaccination coverage in patients with IBD emphasised that the rates of influenza vaccination were low and varied from 19%13 to 28% in adults7,14 and that this rate was only 10% in children 10. However, the vaccination rate in our study was <8%.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…All previously published studies assessing the seasonal influenza vaccination coverage in patients with IBD emphasised that the rates of influenza vaccination were low and varied from 19%13 to 28% in adults7,14 and that this rate was only 10% in children 10. However, the vaccination rate in our study was <8%.…”
Section: Discussioncontrasting
confidence: 67%
“…However, none of these studies had a control arm, and all but one study was performed in adult patients 79. The only paediatric study in patients with IBD was an Australian audit that reviewed medical records 10. In Australia, the annual influenza immunisation is funded for special risk groups, such as children and adolescents with IBD who are ≥6 months of age.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that the most patients with IBD do not receive adequate vaccinations across multiple diff erent healthcare settings ( 7,14,(32)(33)(34)(35)(36)(37)(38)(39)(40). Th is seems to refl ect defi ciencies in provider knowledge both from gastroenterologists and primary care practitioners ( 6,8,41 ).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Two of these studies were retrospective and did not include a control group [36,37]. An Australian study was based on the review of medical records of a random sample of IBD patients (n = 101) [36].…”
Section: Vaccine Coverage In Children With Ibdmentioning
confidence: 99%